ROTARY-WING FLIGHT TESTS TO DETERMINE THE BENEFITS OF FREQUENCY AND SPATIAL DIVERSITY AT THE YUMA PROVING GROUND - Diehl, Michael (International Foundation for Telemetering, 2016)
The United States (U.S.) Army Yuma Proving Ground (YPG) conducted a series of rotary-wing flight tests for the sole purpose of checking out Telemetry data link instrumentation. Four flights were conducted at YPG in February 2016 that built upon an earlier test flight conducted in June 2015. The most recent iteration of testing examined the benefits of frequency diversity on aircraft and the spatial diversity of receiving sites using existing hardware at YPG. Quantitative analysis from those flight results will be presented and include discussion on how results will affect future mission operations at YPG.